2016
DOI: 10.1007/s13202-016-0298-7
|View full text |Cite
|
Sign up to set email alerts
|

Transportation of heavy oils using polymer-stabilized oil-in-water emulsions

Abstract: The increase in demand for crude oil and the depletion of light crude oil reserves have led to increase in the production of heavy crude oils. This has resulted in an interest in decreasing the pumping costs by techniques such as heating, dilution and/or mixing with water. Among the aforementioned methods, emulsification of heavy crude oil with water is the cheapest, and hence, optimizing its application has found increasing attention. This study uses one of the heavy crude oils in Oman to study the viscosity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Higher viscosity values than 0.4 Pa·s result in higher pressure drops in pipeline. To overcome huge pressure drop, pumping power requirement will also increase (Al‐Hashmi et al, 2017; Gudala et al, 2018, 2019b; Hart, 2014; Muñoz et al, 2016). Emulsion droplet size becomes much finer with an increase in surfactant concentration as more surfactant molecules will migrate to oil–water interface increasing elasticity of interfacial film, thereby increasing its ESI and reducing chances of coalescence of droplets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher viscosity values than 0.4 Pa·s result in higher pressure drops in pipeline. To overcome huge pressure drop, pumping power requirement will also increase (Al‐Hashmi et al, 2017; Gudala et al, 2018, 2019b; Hart, 2014; Muñoz et al, 2016). Emulsion droplet size becomes much finer with an increase in surfactant concentration as more surfactant molecules will migrate to oil–water interface increasing elasticity of interfacial film, thereby increasing its ESI and reducing chances of coalescence of droplets.…”
Section: Resultsmentioning
confidence: 99%
“…HCO can be transported through pipelines by reducing viscosity and minimizing wall friction (Hoshyargar and Ashrafizadeh, 2013). Transportation of HCO as O/W emulsion is believed to be the most favorable technique (Al‐Hashmi et al, 2017; Umar et al, 2018). Pure hydrocarbons cannot form stable emulsion with water, the presence of surfactant/additives is essential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Devido às características intrínsecas dos petróleos pesados e extrapesados (alta densidade, alta viscosidade e composição química complexa) (Sun et al, 2017), a produção destes óleos a partir da energia natural do reservatório ou do uso de métodos de recuperação secundária (injeção de água e/ou gás) é inviabilizada (Al-Hashmi et al, 2016). Óleos pesados tendem a apresentar valores de viscosidade entre 10 3 mPa.s a 10 5 mPa.s, em condições ambiente.…”
Section: Introductionunclassified
“…They also reported that quadripolymers have high thermal stability up to 320 °C. Al-Hashmi et al 22 explored the consequence of temperature, oil cut, surfactant, polymer, and salt concentrations, on the rheological behavior of HO (Oman) water emulsions. HO and 70% crude oil emulsion after addition of 3 wt % Triton X-100 displays shear thinning behavior at each temperature.…”
Section: Introductionmentioning
confidence: 99%